Intonational variation and incrementality in listener judgments of ethnicity. Issue 1 (1st April 2020) - Holliday, Nicole; Villarreal, Dan
The current study examines how listeners make gradient and variable ethnolinguistic judgments in an experimental context where the speaker's identity is well-known. It features an open-guise experiment (Soukup, 2013 ) that assessed whether sociolinguistic judgments are subject to incrementality, with judgments increasing in magnitude as variable stimuli demonstrate more extreme differences. In particular, this task tested whether judgments of President Barack Obama as sounding 'more' or 'less' black (e.g., Alim & Smitherman, 2012 ) are sensitive to differences in intonation. Half of critical stimuli featured an L+H* pitch accent, which occurs more frequently in African American Language than in Mainstream U.S. English (Holliday, 2016 ). Four stimuli apiece were created from these phrases by making each pitch accent more extreme by semitone-based F0 steps. Seventy-nine listeners rated these stimuli via the question, "How black does Obama sound here?" Mixed-effects modeling indicated that listeners rated more phonetically extreme L+H* stimuli as sounding blacker, regardless of listener identity. A post-hoc analysis found that listeners attended to different voice quality features in L+H* stimuli. We discuss implications for research in intonation, ethnic identification, incrementality, language attitudes, and sociolinguistic awareness.